Clitellocephalus ophoni (Tuzet et Ormières, 1956) (Apicomplexa: Eugregarinida: Gregarinidae) recorded in Poland on strawberry seed beetle Harpalus(Ophonus) rufipes (De Geer, 1774) (Coleoptera: Carabidae) - Sienkiewicz, Paweł; Lipa, Jerzy (Biological Letters, 2010)
The eugregarine Clitellocephalus ophoni (Tuzet et Ormières, 1956), originally recorded and described on the strawberry seed beetle Harpalus (Ophonus) rufipes (De Geer, 1774) collected in France, is now reported from the same host insect in Poland. It is a new protozoan species in Polish fauna. Out of 280 adult beetles collected in Poland, 21 were parasitized by gregarines, but only 3 by C. ophoni. A morphometric and morphological analysis of C. ophoni trophozoites and gamonts found in the digestive tract of host specimens in France and Poland indicated a significant similarity. The prevalence of C. ophoni is low (about 1%), but the community of gregarines with prevalence of 8% could be an important factor of environmental resistance.